Physical self-esteem of wheelchair basketball players - Samir Qasim; Yaser Telfah; Yazan Haddad (Palacký University Olomouc, 2019)
Background: Physical self has been considered as one of the most important factors that impact global self-esteem. Similarly to global self-esteem, physical self is now widely accepted as a multidimensional construct which contains more specific perceptions across various domains. However, limited research examined physical self of athletes with physical disabilities. Objective: This study, aimed to investigate physical self-esteem of wheelchair basketball players and to explore correlations among various physical domains and physical self-esteem. Methods: Forty one basketball players who participated in West Asian Wheelchair Basketball Championship for the clubs completed Physical Self-Description Questionnaire (PSDQ). It is a 70-item questionnaire that measures physical self-perception across nine domains: Health, Coordination, Activity, Body Fat, Sport Competence, Appearance, Strength, Flexibility, and Endurance. Additionally, this questionnaire assesses each of Physical Self-Esteem and Global Self-Esteem. Pearson correlation coefficient was used to measure these correlations. Results: Study results showed that the participants reported positive perceptions across all physical domains as means ranged from 3.86 to 4.93 (out of 6). The highest mean was 4.93 for global self-esteem followed by physical appearance and body fat (mean 4.75 and 4.70 respectively), whereas physical activity had the lowest mean of 3.86. Furthermore, all domains were significantly correlated to the physical self-esteem. Importantly, coordination accounted for 85.9% and 54.4% of the variance in physical self-esteem and physical activity respectively.Conclusion: This study supports a multidimensional construct of physical self-esteem, suggesting that PSDQ may be applied on the wheelchair basketball players in the Middle East countries.